Further Evidence for the Absence of Polyproline II Stretch in the XAO Peptide - Makowska, Joanna (The Biophysical Society, 2007)
It has been suggested that the alanine-based peptide with sequence Ac-XX-[A](7)-OO-NH(2), termed XAO where X denotes diaminobutyric acid and O denotes ornithine, exists in a predominantly polyproline-helix (P(II)) conformation in aqueous solution. In our recent work, we demonstrated that this “polyproline conformation” should be regarded as a set of local conformational states rather than as the overall conformation of the molecule. In this work, we present further evidence to support this statement. Differential scanning calorimetry measurements showed only a very small peak in the heat capacity of an aqueous solution of XAO at 57°C, whereas the suggested transition to the P(II) structure should occur at ∼30°C. We also demonstrate that the temperature dependence of the (3)J(HNHα) coupling constants of the alanine residues can be explained qualitatively in terms of Boltzmann averaging over all local conformational states; therefore, this temperature dependence proves that a conformational transition does not occur. Canonical MD simulations with the solvent represented by the generalized Born model, and with time-averaged NMR-derived restraints, demonstrate the presence of an ensemble of structures with a substantial amount of local P(II) conformational states but not with an overall P(II) conformation.